Corporate Annual Report vs. Corporate Website: Bridging the Information Differences - Islam, S. M. Faridul; Hossain, Syed Zabid (Asian Business Review, 2023)
Corporate annual reports and websites are vital sources of publicly disclosed company information. However, which is better regarding information richness, ease of use, and cost-effectiveness is still an unsettled issue. The extent of disclosure in these two sources is not the same and differs significantly. To address these information asymmetries between these two sources and make better decisions, many users simultaneously use the annual report and website as their data sources, which is more laborious, time-consuming, and expensive. In the present practice, a company prepares its annual report and then keeps a soft copy on the website. Unlike the current practice, this study proposes a model where corporate transactions and information will first be available on the websites. Then, companies will prepare their annual reports based on the information on their websites. Hence, this study strives to find a way to bridge the information differences between these two information sources by introducing a bridging model that ensures both sources will preserve the same information and the users can use any of them cost-effectively and conveniently without giving any priority to a data source. This research is a step towards sustainable development since our suggested model will save valuable resources, including paper and forest (the demand for printed annual reports will shrink) and various costs, such as materials, time, and labor.